(untitled) (Journal of Computational Mathematics, 1996)
In this paper, we construct unconstrained methods for the generalized nonlinear complementarity problem and variational inequalities. Properties of the correspondent unconstrained optimization problem are studied. We apply these methods to the subproblems in trust region method, and study their interrelationships. Numerical results are also presented.